Elevated copeptin, arterial stiffness, and elevated albumin excretion in adolescents with type 1 diabetes. Issue 8 (29th August 2019) - Wiromrat, Pattara; Bjornstad, Petter; Vinovskis, Carissa; Chung, Linh T.; Roncal, Carlos; Pyle, Laura; Lanaspa, Miguel A.; Johnson, Richard J.; Cherney, David Z.; Reznick‐Lipina, Tyler K.; Bishop, Franziska; Maahs, David M.; et al.
Abstract: Objective: We sought to evaluate copeptin concentrations in adolescents with and without type 1 diabetes (T1D) and examine the associations between copeptin and measures of arterial stiffness and kidney dysfunction. Research design and methods: This analysis included 169 adolescents with T1D (12‐19 years of age, 59% girls, mean HbA1c 9.0 ± 1.5% and diabetes duration of 8.6 ± 2.9 years), in addition to 61 controls without T1D. Arterial stiffness including carotid‐femoral pulse wave velocity (CF‐PWV), carotid‐radial PWV (CR‐PWV), augmentation index normalized to heart rate of 75 bpm (AIx@HR75), and brachial artery distensibility (BAD). Serum copeptin, urinary albumin‐to‐creatinine ratio (UACR), and estimated glomerular filtration rate (eGFR) by serum creatinine and cystatin C were also assessed. Results: Compared to controls, adolescents with T1D had higher median (Q1‐Q3) copeptin (7.5 [5.2‐11.3] vs 6.4 [4.8‐8.3] pmol/L, P = .01), mean ± SD eGFR (121 ± 23 vs 112 ± 16 mL/min/1.73m 2, P = .002) and lower BAD (7.1 ± 1.3 vs 7.2 ± 1.2%, P = .02). Adolescents with T1D in the in high tertile copeptin group (>9.1 pmol/L) had higher AIx@HR75 (10.7 ± 1.2 vs 5 ± 1.2, P = .001), CR‐PWV (5.30 ± 1.0 vs 5.18 ± 1.0 m/s, P = .04), and UACR (12 ± 1 vs 8 ± 1 mg/g, P = .025) compared to those in low tertile (<5.8 pmol/L) after adjusting for age, sex, and eGFR. Copeptin inversely associated with CF‐PWV independent of age, sex, eGFR, SBP, and HbA1c in T1D adolescents. Conclusions: Our data demonstrate that elevated copeptin was associated with worse arterial stiffness in adolescents with T1D. These findings suggest that copeptin could improve CVD risk stratification in adolescents with T1D.